An Analysis of Negotiation Practices in setting Freight Rates for Multinational Company in Indonesia. - Pratomo, Aditya (2010)
The market condition in Indonesia transportation market is slightly different compare to developed countries market such as European or American market. Strong kinship senses had influenced the way they react in business relationship, especially in transportation business, where the solidarity was strong, this is in the sense that if you took care of me, thus I will take care of you. Nestle as the European company in which did not used to this kind of relationship, encounter the difficulty due to the differences in the relationship approach. Hence they chose to manage their relationship to the transporter using modified arm’s-length transactional approach with some modification, since, although it was still driven by the market price, Nestle Indonesia only dealing with several transporters. So it was in the middle of an arm’s-length approach and the collaboration approach. When the oil price was increasing in 2008, their transporter could not afford to do the shipping for Nestle Indonesia, since the operational cost was worsened by the fact that Indonesia government pulled the subsidies on domestic oil price off. They decided to abandon their relationship with Nestle Indonesia and bailed out from the contract. Nestle Indonesia had to re-negotiate to their transporter and fix their relationship with their transporter. Use this particular condition as the case study, this research will try to analyse the Nestle Indonesia’s effort to develop their supply chain relationship towards collaboration and strategic relationship as well as the use of E-auction in the context of transportation business in Indonesia. This research will also try to analyse the decision-making process in Nestle Indonesia in order to understand the reason behind it.